Dampak Pariwisata Terhadap Ekonomi dan Sosial Budaya Masyarakat di Desa Wisata Kenderan - Raditya, Dyota Fajar; Dianasari, Dewa Ayu Made Lily; Subrata, I Made (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This research is to assess how tourism affects the local community, focusing on both economic and socio-cultural aspects. The study targets the household heads of Kenderan Tourism Village, using a purposive sample of 92 respondents. The analysis involves descriptive statistics and confirmatory factor analysis. The findings indicate that the community views tourism development as beneficial for the economy, with an average interval score of 4.73 (strongly agree), suggesting agreement on its positive economic impact. The factor loading for economic indicators is notably high at 0.816. Similarly, the community recognizes a positive socio-cultural impact of tourism, with an average interval score of 4.51 (strongly agree), reflecting agreement on its positive socio-cultural influence. This is reinforced by the highest factor loading in the socio-cultural variables, reaching a total of 0.912